Nigeria’s Leadership Role and ECOWAS Interventions in Cote D’ivoire - Obono, Itam Nnaghe (Kashere Journal of Politics and International Relations, 2024)
ECOWAS abandoned the doctrine of non-interference in the domestic affairs of member States for constructive engagement/non indifference by its interventions in Liberia and Sierra Leone. These 20th century decisive and forceful interventions under the auspices of ECOMOG led by Nigeria earned ECOWAS her pride of place as the first sub-regional economic bloc to venture into regional security roles in the global community. However, the region is still plagued with internal security challenges, terrorism, smuggling, illicit cross border trading and political instability occasioned by: bad governance, electoral violence, lack of free and fair elections, inability of incumbents to accept electoral defeat by opposition, attempts at tenure elongation through constitutional amendments, unconstitutional changes of government and French influence in Francophone states. The reluctance by Nigeria to lead ECOWAS military interventions to restore political stability between 1999 and 2012 in Guinea, Guinea Bissau, and Cote d’Ivoire, reverberated in the continent and global discourse. Many scholars described it as a sign of fatigue and withdrawal by Nigeria from peacekeeping. The return to democracy in May 1999 in Nigeria, after sixteen straight years of military rule, signaled a new approach to Nigeria’s foreign policy without a change of objectives. Nigeria was not visible and did not lead in mediation or deploy militarily in Cote d’Ivoire creating coordination problems.